Effectiveness of cognitive-behavioral theraphy in the treatment of Iranian male drug addicts at a state rehabilitation center - Parvizifard, Aliakbar; Ahmad, Jamaludin; Sulaiman, Tajularipin; Baba, Maznah; Sadeghi, Kheirollah; Moghadam, Arash Parsa (Canadian Center of Science and Education, 2017)
Introduction: The present study aimed at examining the effectiveness of cognitive-behavioral therapy (CBT) group intervention on measures of self-efficacy and level of relapse for abstinence among Iranian male drug addicts. Methods: An experimental research design was adopted in the current study in which the participants consisted of 75 male drug addicts who were consecutively admitted as outpatients at a state rehabilitation center. They were randomly allocated to experimental (N=37) and control (N=38) groups. They completed the Iranian version of Drug Taking Confidence Questionnaire (DTCQ-IV) and took urine test as pre-test and post-test. The CBT group intervention was conducted at 12 sessions, one session per week. It was hypothesized that there were significant differences between the experimental and control groups regarding self-efficacy and level of relapse. Result: The results of ANCOVA showed there were significant differences in pleasant emotion and testing control between the two groups on measures of self-efficacy. The results of McNemar test indicated level of relapse in the experimental group significantly declined from pre-test to post-test. Furthermore, using Chi-square analysis, a significant difference (with a moderate effect size) was found in the levels of relapse. Conclusion: The present study provides strong support for CBT group intervention as an effective treatment for Iranian male drug addicts. Therefore, CBT group intervention can be considered as a practical approach in the treatment of people with SUDs.